Barriers and enablers for the implementation of trauma-informed care in healthcare settings: a systematic review - Yan Huo; Leah Couzner; Tim Windsor; Kate Laver; Nadeeka N. Dissanayaka; Monica Cations (Implementation Science Communications, 2023)
Abstract Background Healthcare services can be re-traumatising for trauma survivors where they trigger memories of past distressing events and exert limits to a survivor’s sense of autonomy, choice, and control. The benefits of receiving trauma-informed healthcare are well established; however, factors that promote or impede the implementation of trauma-informed care are not yet well characterised and understood. The aim of this review was to systematically identify and synthesise evidence regarding factors that promote or reduce the implementation of TIC in healthcare settings. Methods This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2.0 guidelines. Scopus, MEDLINE, Proquest, PsycINFO and grey literature were searched for original research or evaluations published between January 2000 and April 2021 reporting barriers and/or facilitating factors for the implementation of trauma-informed care in a healthcare setting. Two reviewers independently assessed the quality of each included study using the Mixed Methods Appraisal Tool (MMAT) Checklist. Results Twenty-seven studies were included, 22 of which were published in the USA. Implementation occurred in a range of health settings, predominantly mental health services. The barriers and facilitators of implementing trauma-informed care were categorised as follows: intervention characteristics (perceived relevance of trauma-informed care to the health setting and target population), influences external to the organisation (e.g. interagency collaboration or the actions of other agencies) and influences within the organisation in which implementation occurred (e.g. leadership engagement, financial and staffing resources and policy and procedure changes that promote flexibility in protocols). Other factors related to the implementation processes (e.g. flexible and accessible training, service user feedback and the collection and review of initiative outcomes) and finally the characteristics of individuals within the service or system such as a resistance to change. Conclusions This review identifies key factors that should be targeted to promote trauma-informed care implementation. Continued research will be helpful for characterising what trauma-informed care looks like when it is delivered well, and providing validated frameworks to promote organisational uptake for the benefit of trauma survivors. Registration The protocol for this review was registered on the PROSPERO database (CRD42021242891).